Re-Educative Da'wah Communication for the Deradicalization of Radicalized Prisoners in Jepara, Indonesia - Wahyu Khoiruz Zaman (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
Radicalism and terrorism in Indonesia remain an unresolved threat. One of the Indonesian government's efforts to address this issue is through a deradicalization program. Although not a region with the highest threat level, Jepara Regency, as one of Indonesia's regencies, is not immune to the problem of radicalism and terrorism. The purpose of this study is to describe effective da'wah strategies for deradicalizing radical/terrorist prisoners. This study uses a qualitative approach to gain a deeper understanding of the re-education da'wah strategy in the effort to deradicalize radical prisoners in Jepara, Central Java. This study adopted a case study design, which allowed researchers to intensively and comprehensively gather information about the re-education da'wah strategy implemented in Jepara. Primary data collection was conducted through in-depth interviews with da'i (re-education facilitators) and relevant stakeholders. This study concludes that radicalism prisoners in Jepara, Indonesia were successfully neutralized from radical thoughts before acts of terrorism occurred by law enforcement officers together with stakeholders, namely the Indonesian Ulema Council (MUI) and the youth organization GP.Ansor through a re-education da'wah communication.